2020
DOI: 10.20885/ajim.vol2.iss2.art6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of financial performance and macroeconomic on financing risk in Islamic banks

Abstract: The aim of this research is to identify the influence of microeconomic and macroeconomic variables toward non-performing financing of Islamic Commercial Banks in Indonesia.Methodology: Microeconomic variables include CAR, FDR, BOPO, ROA, while macroeconomic variables include IPI, BI Rate, Inflation and SBIS for the period of 2015 to 2019. The data analysis method in this study is auto-regressive distributed lag (ARDL) using EViews 10 tool which can analyze the relationship between independent and dependent var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In this case, the control carried out by the Indonesian central bank (2021), indicating that the BIR had a negative sign and relevantly impacted NPFs. Meanwhile, Angraini and Anindita (2020); Hasanah and Septiarini (2020); Sudarsono (2018) found that the BIR was ineffective on the NPFs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the control carried out by the Indonesian central bank (2021), indicating that the BIR had a negative sign and relevantly impacted NPFs. Meanwhile, Angraini and Anindita (2020); Hasanah and Septiarini (2020); Sudarsono (2018) found that the BIR was ineffective on the NPFs.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in GDP per capita also affect financing risk, with increased income leading to smaller monetary uncertainty due to the ability of people to pay loans and vice versa (Angraini & Anindita, 2020;Muqorrobin et al, 2021). Meanwhile, rising or falling inflation and benchmark loan rates (BIR) influence risks in the real sector business, leading to an effect on financing.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the smaller the BOPO ratio means the more efficient the bank's operational performance in carrying out its daily operations so that the probability of a bank in difficult conditions will be smaller. Research conducted by Angraini et al (2020), Auliani and Syaichu (2016), Fatoni and Utami (2019), Rahman and Fatmawati (2020), Santosa et al (2014), and Wibowo and Saputra (2017) states that BOPO has a positive effect on non-performing financing in banks.…”
Section: Relationship Between Financing To Deposit Ratio (Fdr) and Non-performing Financing (Npf)mentioning
confidence: 99%
“…Therefore, the higher the inflation rate in a country will cause non-performing financing to increase. According to research conducted by Angraini et al (2020), and Hosen and Muhari (2019), inflation affects the level of non-performing financing.…”
Section: Relationship Between Financing To Deposit Ratio (Fdr) and Non-performing Financing (Npf)mentioning
confidence: 99%